Super-lubricating and corrosion-resistant DLC (diamond-like carbon) protective coating and preparation method thereof

By introducing a multi-layer composite structure into the DLC coating and utilizing magnetron sputtering and magnetically filtered arc ion plating processes, the problem of insufficient bonding strength of the DLC coating under high internal stress is solved, thereby improving its super-lubricating and wear-resistant properties, making it suitable for a variety of industrial applications.

CN120796907APending Publication Date: 2025-10-17NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510960626.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-11
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

Existing DLC ​​coatings have insufficient bonding strength under high internal stress, making it difficult to achieve ultra-low friction and simultaneously optimize wear resistance and lubrication. Conventional methods also present difficulties in process control, affecting their application under harsh working conditions.

Method used

A multi-layer composite coating was prepared on a substrate using magnetron sputtering and magnetically filtered arc ion plating. By doping with transition metal and non-metal elements, a cleaning modification layer, a Cr/CrC gradient transition layer, a Cr-DLC bonding reinforcement layer, a Si-DLC main functional layer, and a MoS2-DLC surface lubrication layer were formed, which reduced internal stress and enhanced bonding strength and lubricity.

Benefits of technology

A super-lubricating and wear-resistant DLC protective coating has been achieved, which has high hardness, good bonding strength and friction performance, and is suitable for a variety of industrial applications and industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120796907A_ABST
    Figure CN120796907A_ABST
Patent Text Reader

Abstract

The invention discloses a super-lubricating and corrosion-resistant DLC (diamond-like carbon) protective coating and a preparation method thereof, and belongs to the technical field of protective coatings. The coating is prepared on a base body through magnetron sputtering and magnetic filtering arc ion plating processes, a multi-layer composite structure is formed by doping transition metal elements and non-metal elements, and the multi-layer composite structure comprises a cleaning modification layer, a gradient transition layer, a combination strengthening layer, a main functional layer and a surface lubricating layer. Through element doping, the internal stress of the DLC coating is effectively reduced, the surface lubricity is enhanced, the bonding strength of the coating and a matrix is improved, and meanwhile the high hardness and excellent wear resistance of the DLC coating are reserved. In addition, the preparation process is simple, is suitable for industrial production, and can be widely applied to surface protection in the fields of molds, automobiles, aerospace and the like.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of functional protective coating materials, and particularly relates to a super-lubricating and abrasion-resistant DLC protective coating and a preparation method thereof. BACKGROUND

[0002] The diamond-like carbon (DLC) coating is highly concerned in the field of surface protection due to its high hardness, good wear resistance and low friction coefficient, but its application is still limited by the insufficient bonding strength caused by high internal stress, the difficulty in achieving ultra-low friction under harsh working conditions, and the contradiction between the single structure or doping and the optimization of wear resistance and lubricity. The conventional method such as single element doping can alleviate the internal stress but may sacrifice the hardness or corrosion resistance, the addition of a solid lubricating phase (MoS2) can reduce the friction coefficient but often weakens the wear resistance, and the complex multi-layer structure design affects the reliability and industrial application if the interface bonding is poor or the process control is difficult. Therefore, it is urgent to develop a new type of DLC composite coating structure with super-lubrication, strong bonding, high wear resistance and feasible process and an efficient preparation method thereof. SUMMARY

[0003] The application is to solve the above technical problems, and proposes a super-lubricating and abrasion-resistant DLC protective coating and a preparation method thereof. The coating is prepared on a substrate by a magnetron sputtering and a magnetic filtering arc ion plating process, and a multi-layer composite structure is formed by doping transition metal elements and non-metal elements. The element doping can effectively reduce the internal stress of the DLC coating, enhance the surface lubricity, improve the bonding strength of the coating and the substrate, and at the same time, the high hardness and excellent wear resistance of the DLC coating are retained, which is suitable for various industrial application scenarios.

[0004] A super-lubricating and abrasion-resistant DLC protective coating, the coating comprises from the substrate outwardly: a cleaning modification layer, a Cr / CrC gradient transition layer, a Cr-DLC bonding strengthening layer, a Si-DLC main functional layer, and a MoS2-DLC surface lubricating layer.

[0005] The thickness of the cleaning modification layer is 0.05-0.1 μm, and the cleaning modification layer is prepared by a high-bias argon ion bombardment process.

[0006] The thickness of the Cr / CrC gradient transition layer is 0.25-0.3 μm.

[0007] The thickness of the Cr-DLC bonding strengthening layer is 0.2-0.25 μm, and the hardness is 20-35 GPa.

[0008] The thickness of the Si-DLC main functional layer is 0.15-0.25 μm, and the hardness is 15-30 GPa.

[0009] The MoS2-DLC surface lubricating layer has a thickness of 0.2-0.3 μm, a hardness of 12-18 GPa, and a friction coefficient of 0.05-0.08.

[0010] In addition, the application further provides a preparation method of the super-lubricating and abrasion-resistant DLC protective coating.

[0011] Step S1: pretreating the substrate;

[0012] Step S2: cleaning and modifying the surface of the substrate to remove surface impurities and improve surface activity;

[0013] Step S3: depositing a Cr / CrC gradient transition layer on the cleaning and modification layer by using a magnetic filter arc ion plating process;

[0014] Step S4: depositing a Cr-DLC binding strengthening layer on the gradient transition layer by using a non-equilibrium multi-target magnetron sputtering method;

[0015] Step S5: depositing a Si-DLC main functional layer on the binding strengthening layer by using a non-equilibrium multi-target magnetron sputtering method;

[0016] Step S6: depositing a MoS2-DLC surface lubricating layer on the main functional layer by using a non-equilibrium multi-target magnetron sputtering method;

[0017] Step S7: taking out the sample after the temperature drops to room temperature to obtain the protective coating.

[0018] Further, the specific steps of the substrate pretreatment in step S1 are as follows: polishing the substrate by using 400#, 800# and 1400# sandpaper in sequence, and then polishing the substrate by using W1.5 and W0.5 diamond grinding paste in sequence; cleaning the polished substrate by using acetone and anhydrous ethanol in sequence for 10-20 min, and then blowing dry with dry nitrogen and placing on a turntable.

[0019] Further, the cleaning and modification process parameters of the substrate surface in step S2 are as follows:

[0020] The temperature is 150-200 ℃, the bias voltage is -900 V, the duty cycle is 10%, the gas pressure is 2.5-3.0 Pa, the Ar flow rate is 500 sccm, and the time is 60 min.

[0021] Further, the deposition process parameters of the Cr / CrC gradient transition layer in step S3 are as follows:

[0022] The temperature is 150-200 DEG C, the bias voltage is -150V, the duty cycle is 60%, the air pressure is 0.8Pa, the Ar flow is 200sccm, the pulse DC power is 6kw, and the total deposition time is 10 minutes.

[0023] Further, the deposition process step of the Cr / CrC gradient transition layer in the step S3 is as follows: the C2H2 valve is opened to start 2sccm acetylene at the 4th minute after the deposition starts; the C2H2 valve is adjusted to start 4sccm acetylene at the 6th minute after the deposition starts; and the C2H2 valve is adjusted to start 6sccm acetylene at the 8th minute after the deposition starts.

[0024] Further, the deposition process parameters of the Cr-DLC combined strengthening layer in the step S4 are as follows:

[0025] The flow rate of argon is 60-90sccm, the working air pressure is kept at 0.5Pa-1.0Pa, the substrate bias voltage is -50--250V, the purity of the graphite target is 99.999%, the average target current is 0.4-0.6A, the purity of the Si target is 99.999%, the average target current is 0.1-0.2A, and the deposition time is 20-60 minutes.

[0026] Further, the deposition process parameters of the Si-DLC main functional layer in the step S5 are as follows:

[0027] The flow rate of argon is 60-90sccm, the working air pressure is kept at 0.5Pa-1.0Pa, the substrate bias voltage is -50--250V, the purity of the graphite target is 99.999%, the average target current is 0.4-0.6A, the purity of the Si target is 99.999%, the average target current is 0.1-0.2A, and the deposition time is 20-60 minutes.

[0028] Further, the deposition process parameters of the MoS2-DLC surface lubricating layer in the step S6 are as follows:

[0029] The flow rate of argon is 60-90sccm, the working air pressure is kept at 0.3Pa-0.6Pa, the substrate bias voltage is -50--250V, the purity of the graphite target is 99.999%, the purity of the MoS2 target is 99.95%, and the deposition time is 20-60 minutes.

[0030] Further, the unbalanced multi-target magnetron sputtering method in the steps S4, S5 and S6 utilizes an electric field and an asymmetric magnetic field to control plasma, and realizes thin film deposition by combining multi-target synergistic sputtering.

[0031] Compared with the prior art, the application can achieve the following beneficial effects:

[0032] (1) The super-lubrication and abrasion-resistant DLC protective coating and the preparation method thereof proposed by the application adopt pulse direct current magnetron sputtering and magnetic filtering arc ion plating process to prepare a multilayer coating on a substrate, and the initial bonding strength of the protective coating is effectively improved through a Cr / CrC transition layer.

[0033] (2) The super-lubrication and abrasion-resistant DLC protective coating and the preparation method thereof proposed by the application make the protective coating have higher toughness and stress release capacity through a Cr-DLC combined reinforcement layer.

[0034] (3) The super-lubrication and abrasion-resistant DLC protective coating and the preparation method thereof proposed by the application reduce the internal stress of the protective coating while maintaining the mechanical strength of the protective coating through a Si-DLC main functional layer, and have both hardness and strain buffering characteristics.

[0035] (4) The super-lubrication and abrasion-resistant DLC protective coating and the preparation method thereof proposed by the application provide interfacial lubrication through a MoS2-DLC surface lubricating layer, and improve the friction performance of the protective coating.

[0036] (5) The super-lubrication and abrasion-resistant DLC protective coating preparation process proposed by the application is simple, convenient to operate, and suitable for industrialized production. The super-lubrication and abrasion-resistant DLC protective coating has wide applicability, and can be widely applied to the surface protection of cutting tools, aerospace components and other components that need to work stably for a long time in extreme friction, wear or corrosion environment. BRIEF DESCRIPTION OF DRAWINGS

[0037] Figure 1 is a structural schematic diagram of the super-lubrication and abrasion-resistant DLC protective coating;

[0038] Figure 2 is a preparation flowchart of the super-lubrication and abrasion-resistant DLC protective coating;

[0039] Figure 3 is a cross-sectional SEM diagram of the super-lubrication and abrasion-resistant DLC protective coating. DETAILED DESCRIPTION

[0040] The specific embodiments of the application will be further described below with reference to the accompanying drawings, and the technical solutions in the embodiments of the application will be clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the application, rather than all the embodiments. Based on the embodiments in the application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the application.

[0041] In combination with Figure 1The present invention proposes a super lubricating and wear-resistant DLC protective coating, which comprises, from the substrate outward, a cleaning modification layer, a Cr / CrC gradient transition layer, a Cr-DLC bonding strengthening layer, a Si-DLC main functional layer, and a MoS2-DLC surface lubricating layer;

[0042] The cleaning modified layer has a thickness of 0.05 to 0.1 μm and is prepared by a high bias argon ion bombardment process;

[0043] The thickness of the Cr / CrC gradient transition layer is 0.25 to 0.3 μm;

[0044] The Cr-DLC bonding strengthening layer has a thickness of 0.2 to 0.25 μm and a hardness of 20 to 35 GPa;

[0045] The thickness of the Si-DLC main functional layer is 0.15 to 0.25 μm, and the hardness is 15 to 30 GPa;

[0046] The MoS2-DLC surface lubricating layer has a thickness of 0.2 to 0.3 μm, a hardness of 12 to 18 GPa, and a friction coefficient of 0.05 to 0.08.

[0047] Combine Figure 2 The present invention also provides a method for preparing a super-lubricating and wear-resistant DLC protective coating, wherein the super-lubricating and wear-resistant DLC protective coating specifically comprises the following steps:

[0048] Step S1, pre-treating the substrate;

[0049] Step S2: cleaning and modifying the substrate surface to remove surface impurities and improve surface activity;

[0050] Step S3: using a magnetic filtered arc ion plating process to deposit a Cr / CrC gradient transition layer on the cleaned modified layer;

[0051] Step S4: using an unbalanced multi-target magnetron sputtering method to deposit a Cr-DLC bonding strengthening layer on the gradient transition layer;

[0052] Step S5: using an unbalanced multi-target magnetron sputtering method to deposit a Si-DLC main functional layer on the bonding strengthening layer;

[0053] Step S6: using an unbalanced multi-target magnetron sputtering method to deposit a MoS2-DLC surface lubricating layer on the main functional layer;

[0054] Step S7: After the temperature drops to room temperature, take out the sample to obtain a protective coating. The SEM image of the cross section of the protective coating is as follows: Figure 3 shown.

[0055] Further, the specific step of the step S1 is that the substrate is polished by using 400#, 800# and 1400# sandpaper in sequence, and then polished by using W1.5 and W0.5 diamond polishing paste in sequence; the polished substrate is cleaned by using acetone and anhydrous ethanol in sequence for 10-20 min, and then dried by using dry nitrogen and placed on a turntable.

[0056] Further, the substrate surface is cleaned and modified in the step S2, and the cleaning process parameters are as follows:

[0057] The temperature is 150-200℃, the bias voltage is-900V, the duty cycle is 10%, the gas pressure is 2.5-3.0Pa, the Ar flow rate is 500sccm, and the time is 60 min.

[0058] Further, the deposition process parameters of the Cr / CrC gradient transition layer in the step S3 are as follows:

[0059] The temperature is 150-200℃, the bias voltage is-150V, the duty cycle is 60%, the gas pressure is 0.8Pa, the Ar flow rate is 200sccm, the pulsed direct current power is 6kw, and the total deposition time is 10 min.

[0060] Further, the deposition process steps of the Cr / CrC gradient transition layer in the step S3 are as follows: the C2H2 valve is opened to start the input of 2sccm acetylene at the 4th min after the deposition starts; the C2H2 valve is adjusted to input 4sccm acetylene at the 6th min after the deposition starts; the C2H2 valve is adjusted to input 6sccm acetylene at the 8th min after the deposition starts.

[0061] Further, the deposition process parameters of the Cr-DLC combined strengthening layer in the step S4 are as follows:

[0062] The Ar flow rate is 60-90sccm, the working gas pressure is kept at 0.5-1.0Pa, the substrate bias voltage is-50--250V, the graphite target purity is 99.999%, the target average current is 0.4-0.6A, the Si target purity is 99.999%, the target average current is 0.1-0.2A, and the deposition time is 20-60 min.

[0063] Further, the deposition process parameters of the Si-DLC main functional layer in the step S5 are as follows:

[0064] The Ar flow rate is 60-90sccm, the working gas pressure is kept at 0.5-1.0Pa, the substrate bias voltage is-50--250V, the graphite target purity is 99.999%, the target average current is 0.4-0.6A, the Si target purity is 99.999%, the target average current is 0.1-0.2A, and the deposition time is 20-60 min.

[0065] Further, the deposition process parameters of the MoS2-DLC surface lubricating layer in the step S6 are as follows:

[0066] The flow rate of argon is 60-90sccm, the working gas pressure is kept at 0.3Pa-0.6Pa, the substrate bias is -50--250V, the purity of the graphite target is 99.999%, the purity of the MoS2 target is 99.95%, and the deposition time is 20-60min.

[0067] Further, the non-equilibrium multi-target magnetron sputtering method in the steps S4, S5 and S6 utilizes an electric field and an asymmetric magnetic field to control plasma, and realizes thin film deposition in combination with multi-target collaborative sputtering.

[0068] The present application proposes the following specific embodiments:

[0069] Embodiment 1:

[0070] An ultra-lubricating and abrasion-resistant DLC protective coating is prepared by the following steps:

[0071] S1: Pretreatment: the surface of the substrate is polished by using W1.5 and W0.5 diamond grinding paste in sequence after polishing with 400#, 800# and 1400# sandpaper in sequence. The polished substrate is ultrasonically cleaned in acetone and anhydrous ethanol for 5min, and then dried by using dry argon;

[0072] S2: The surface of the substrate is subjected to cleaning and modification treatment to remove surface impurities and improve surface activity; the cleaning process parameters are as follows:

[0073] The temperature is 150-200℃, the bias is -900V, the duty cycle is 10%, the gas pressure is 2.5-3.0Pa, the Ar flow rate is 500sccm, and the time is 60min;

[0074] S3: A Cr / CrC gradient transition layer is deposited on the cleaning and modification layer, and the deposition process parameters are as follows:

[0075] The temperature is 150-200℃, the bias is -150V, the duty cycle is 60%, the gas pressure is 8.0x10 -1 Pa, the Ar flow rate is 200sccm, the pulsed direct current power source power is 6kw, the total deposition time is 10min; the C2H2 valve is opened to start passing 2sccm of acetylene at the 4min after the start of deposition; the C2H2 valve is adjusted to pass 4sccm of acetylene at the 6min after the start of deposition; the C2H2 valve is adjusted to pass 6sccm of acetylene at the 8min after the start of deposition;

[0076] S4: Cr-DLC layer was further deposited on the surface by using unbalanced multi-target magnetron sputtering method with 99.95% pure Cr target and 99.999% pure graphite target as raw materials, and argon was introduced, the flow rate of argon was 90sccm, the working pressure was kept at 1.0Pa, the substrate bias was -250V, the average current of the graphite target was 0.6A, the average current of the Cr target was 0.2A, and the deposition time was 60min;

[0077] S5: Si-DLC layer was prepared on the Cr-DLC layer by using unbalanced multi-target magnetron sputtering method with 99.999% pure Si target and 99.999% pure graphite target as raw materials, and argon was introduced, the flow rate of argon was 90sccm, the working pressure was kept at 1.0Pa, the substrate bias was -250V, the average current of the graphite target was 0.6A, the average current of the Si target was 0.2A, and the deposition time was 60min;

[0078] S6: 99.999% graphite target (DC 0.6A, Ar environment) and 99.95% MoS2 target (RF 150W, Ar environment) were used as raw materials, 90sccm argon was introduced, the working pressure was controlled at 0.5Pa, a substrate bias of -150V was applied, and the deposition time was 40min;

[0079] S7: After the temperature dropped to room temperature, the sample was taken out to obtain the protective coating.

[0080] The obtained super-lubricating and abrasion-resistant DLC protective coating has a friction coefficient of 0.08.

[0081] Example 2:

[0082] A super-lubricating and abrasion-resistant DLC protective coating was prepared by the following steps:

[0083] S1: Pretreatment: the surface of the substrate was polished with 400#, 800# and 1400# sandpaper in sequence, and then polished with W1.5 and W0.5 diamond polishing paste in sequence. The polished substrate was ultrasonically cleaned in acetone and anhydrous ethanol for 5min, and then dried with dry argon;

[0084] S2: The surface of the substrate was cleaned and modified to remove surface impurities and improve surface activity; the cleaning process parameters were as follows:

[0085] The temperature was 150-200℃, the bias was -900V, the duty cycle was 10%, the gas pressure was 2.5-3.0Pa, the Ar flow rate was 500sccm, and the time was 60min;

[0086] S3: Cr / CrC gradient transition layer was deposited on the cleaning and modification layer, and the deposition process parameters were as follows:

[0087] The temperature is 150-200 DEG C, the bias voltage is -150V, the duty cycle is 60%, the air pressure is 0.8Pa, the Ar flow is 200sccm, the pulse DC power is 6kw, and the total deposition time is 10min; the C2H2 valve is opened to start passing 2sccm acetylene at the 4th min after the deposition starts; the C2H2 valve is adjusted to pass 4sccm acetylene at the 6th min after the deposition starts; the C2H2 valve is adjusted to pass 6sccm acetylene at the 8th min after the deposition starts;

[0088] S4: An unbalanced multi-target magnetron sputtering method is adopted, 99.95% pure Cr targets and 99.999% pure graphite targets are used, and argon is passed, the argon flow is 60sccm, the working air pressure is kept at 0.5Pa, the substrate bias voltage is -50V, the average current of the graphite target is 0.4A, the average current of the Cr target is 0.1A, a Cr-DLC layer is further deposited on the surface, and the deposition time is 20min;

[0089] S5: An unbalanced multi-target magnetron sputtering method is adopted, 99.999% pure Si targets and 99.999% pure graphite targets are used, and argon is passed, the argon flow is 60sccm, the working air pressure is kept at 0.5Pa, the substrate bias voltage is -50V, the average current of the graphite target is 0.4A, the average current of the Si target is 0.1A, a Si-DLC layer is prepared on the Cr-DLC layer, and the deposition time is 20min;

[0090] S6: An unbalanced magnetron sputtering method is adopted, 99.999% graphite targets (DC 0.6A, Ar environment) and 99.95% MoS2 targets (RF 150W, Ar environment) are used as raw materials, 90sccm argon is passed, the working air pressure is controlled to be 0.5Pa, a substrate bias voltage of -150V is applied, and the deposition time is 40min;

[0091] S7: The sample is taken out after the temperature is reduced to room temperature, and a protective coating is obtained.

[0092] The obtained super-lubricating and abrasion-resistant DLC protective coating has a friction coefficient of 0.08.

[0093] The above only describes the preferred embodiments of the application, and the application is not limited to the above embodiments. It can be understood that other improvements and changes directly derived or thought of by those skilled in the art without departing from the spirit and concept of the application should be considered to be included in the protection scope of the application.

Claims

1. A super lubricating and wear-resistant DLC protective coating, characterized in that: The coating comprises, from the substrate outward, a cleaning and modification layer, a Cr / CrC gradient transition layer, a Cr-DLC bonding and strengthening layer, a Si-DLC main functional layer, and a MoS2-DLC surface lubricating layer; The cleaning modified layer has a thickness of 0.05 to 0.1 μm and is prepared by a high bias argon ion bombardment process; The thickness of the Cr / CrC gradient transition layer is 0.25 to 0.3 μm; The Cr-DLC bonding strengthening layer has a thickness of 0.2 to 0.25 μm and a hardness of 20 to 35 GPa; The thickness of the Si-DLC main functional layer is 0.15 to 0.25 μm, and the hardness is 15 to 30 GPa; The MoS2-DLC surface lubricating layer has a thickness of 0.2 to 0.3 μm, a hardness of 12 to 18 GPa, and a friction coefficient of 0.05 to 0.

08.

2. A method for preparing a super lubricating and wear-resistant DLC protective coating, characterized in that: The method for preparing a super-lubricating and wear-resistant DLC protective coating is applied to a super-lubricating and wear-resistant DLC protective coating according to claim 1, and the super-lubricating and wear-resistant DLC protective coating specifically comprises the following steps: Step S1, pre-treating the substrate; Step S2: cleaning and modifying the substrate surface to remove surface impurities and improve surface activity; Step S3: using a magnetic filtered arc ion plating process to deposit a Cr / CrC gradient transition layer on the cleaned modified layer; Step S4: using an unbalanced multi-target magnetron sputtering method to deposit a Cr-DLC bonding strengthening layer on the gradient transition layer; Step S5: using an unbalanced multi-target magnetron sputtering method to deposit a Si-DLC main functional layer on the bonding strengthening layer; Step S6: using an unbalanced multi-target magnetron sputtering method to deposit a MoS2-DLC surface lubricating layer on the main functional layer; Step S7: After the temperature drops to room temperature, the sample is taken out to obtain a protective coating.

3. The method for preparing a super lubricating and wear-resistant DLC protective coating according to claim 2, characterized in that: The specific steps of the substrate pretreatment in step S1 are: grinding the substrate with 400#, 800#, and 1400# sandpaper in sequence, and then polishing the substrate with W1.5 and W0.5 diamond grinding pastes in sequence; ultrasonically cleaning the polished substrate with acetone and anhydrous ethanol for 10 to 20 minutes each, and then drying it with dry nitrogen and placing it on a rotating rack.

4. The method for preparing a super lubricating and wear-resistant DLC protective coating according to claim 2, characterized in that: In step S2, the substrate surface is cleaned and modified, and the cleaning process parameters are: The temperature is 150-200° C., the bias voltage is -900 V, the duty cycle is 10%, the gas pressure is 2.5-3.0 Pa, the Ar flow rate is 500 sccm, and the time is 60 min.

5. The method for preparing a super lubricating and wear-resistant DLC protective coating according to claim 2, characterized in that: The deposition process parameters of the Cr / CrC gradient transition layer in step S3 are: The temperature is 150-200° C., the bias voltage is -150 V, the duty cycle is 60%, the gas pressure is 0.8 Pa, the Ar flow rate is 200 sccm, the pulsed DC power supply power is 6 kW, and the total deposition time is 10 min.

6. The method for preparing a super lubricating and wear-resistant DLC protective coating according to claim 2, characterized in that: In step S3, the magnetic filtered arc ion plating process realizes film deposition by arc evaporation of target material and magnetic filtered particles; The deposition process steps of the Cr / CrC gradient transition layer are as follows: 4 minutes after the start of deposition, the C2H2 valve is opened and 2 sccm acetylene is introduced; 6 minutes after the start of deposition, the C2H2 valve is adjusted and 4 sccm acetylene is introduced; 8 minutes after the start of deposition, the C2H2 valve is adjusted and 6 sccm acetylene is introduced.

7. The method for preparing a super lubricating and wear-resistant DLC protective coating according to claim 2, characterized in that: The process parameters for the Cr-DLC combined strengthening layer deposition in step S4 are: The argon flow rate is 60 to 90 sccm, the working gas pressure is maintained at 0.5 Pa to 1.0 Pa, the substrate bias is -50 to -250 V, the graphite target purity is 99.999%, the target average current is 0.4 to 0.6 A, the Si target purity is 99.999%, the target average current is 0.1 to 0.2 A, and the deposition time is 20 to 60 min.

8. The method for preparing a super lubricating and wear-resistant DLC protective coating according to claim 2, characterized in that: The deposition process parameters of the Si-DLC main functional layer in step S5 are: The argon flow rate is 60 to 90 sccm, the working gas pressure is maintained at 0.5 Pa to 1.0 Pa, the substrate bias is -50 to -250 V, the graphite target purity is 99.999%, the target average current is 0.4 to 0.6 A, the Si target purity is 99.999%, the target average current is 0.1 to 0.2 A, and the deposition time is 20 to 60 min.

9. The method for preparing a super lubricating and wear-resistant DLC protective coating according to claim 2, characterized in that: The process parameters for depositing the MoS2-DLC surface lubricating layer in step S6 are: The flow rate of argon gas is 60 to 90 sccm, the working gas pressure is maintained at 0.3 Pa to 0.6 Pa, the substrate bias voltage is -50 to -250 V, the purity of the graphite target is 99.999%, the purity of the MoS2 target is 99.95%, and the deposition time is 20 to 60 min.

10. The method for preparing a super lubricating and wear-resistant DLC protective coating according to claim 2, characterized in that: The unbalanced multi-target magnetron sputtering method in steps S4, S5, and S6 utilizes electric field and asymmetric magnetic field to control plasma, and combines multi-target coordinated sputtering to achieve thin film deposition.

Citation Information

Cited By

  • Lubricating and wear-resisting treatment method for plunger pair of plunger pump based on vacuum vapor deposition

    CN121273614A